Comparison of faecal microbiota in Blastocystis-positive and Blastocystis-negative irritable bowel syndrome patients. Issue 1 (December 2016) - Nagel, Robyn; Traub, Rebecca; Allcock, Richard; Kwan, Marcella; Bielefeldt-Ohmann, Helle
Abstract Background We investigated whether the carriage ofBlastocystis in IBS patients was associated with differences in the faecal microbiota. Forty patients with diarrhoea-predominant IBS (26Blastocystis -positive and 14Blastocystis -negative) and 57 healthy controls (HC) (42Blastocystis -positive and 15Blastocystis -negative) submitted faecal samples for metataxonomic analysis of the 16S ribosomal RNA gene. Differences in the relative abundance of bacteria in these IBS and HC groups were evaluated from phylum to genus level. Results Significant changes were observed in two dominant phyla in IBS patients, regardless ofBlastocystis infection status, namely a rise in Firmicutes and a statistically significant reduction in relative abundance of Bacteroidetes (with a threefold increase in the Firmicutes to Bacteoridetes ratio). Significant differences at genus level in IBS subjects compared to HC were also observed for many bacterial species. However, further clinical subgroup analysis ofBlastocystis -positive andBlastocystis- negative subjects, regardless of symptoms, showed no significant differences at the phylum or genus level in IBS-P compared to IBS-N. Conclusions Significant differences in the faecal microbiota between diarrhoea-predominant IBS patients and healthy controls were confirmed, but the carriage ofBlastocystis did not significantly alter the faecal microbiota. IfBlastocystis -positive patients represent a separate clinical subtype of IBS, this group is not identified by changes in the microbiota.